THE INFLUENCE OF THE TEACHER'S ROLE IN LEARNING HISTORY ON STUDENTS' NATIONALISM VALUES AT GORONTALO BAKTI NUSANTARA HEALTH SCHOOL - Pakaya, Dela; Yunus, Resmiyati; Manay, Helman (CV. Fahr Publishing, 2025)
Nationalism is an important value that must be instilled in the younger generation to strengthen their identity and awareness as Indonesian citizens. History teachers play an important role in instilling nationalist values through effective learning. Bakti Nusantara Gorontalo Health Vocational School as a vocational education institution must play an important role in developing student nationalism. The aim of this research is to find out how history is taught at the Bakti Nusantara Gorontalo Health Vocational School, to find out the role of teachers in instilling an attitude of Nationalism, the obstacles faced by history teachers at the Bakti Nusantara Gorontalo Health Vocational School in instilling an attitude of Nationalism. The research method used is a qualitative method using data sources from interviews, observation and documentation of this research. The research results show that history learning is aimed at providing a comprehensive understanding of Indonesian history. Knowing the role of teachers in instilling an attitude of nationalism shows that the role of teachers in instilling an attitude of nationalism through history lessons at the Bakti Nusantara Gorontalo Health Vocational School is very important. This effort is realized through various comprehensive learning strategies, with an updated curriculum that incorporates history learning into class XI. The obstacles faced by history teachers at the Gorontalo Health Vocational School in cultivating an attitude of nationalism include limited learning time. Other obstacles include the geographical location of the school which is around a main road, as well as the lack of high walls as a barrier for students who want to play truant or not attend. lesson hours.